2014
DOI: 10.1094/phyto-04-13-0106-r
|View full text |Cite
|
Sign up to set email alerts
|

Identification of a Hidden Resistance Gene in Tetraploid Wheat Using Laboratory Strains of Pyricularia oryzae Produced by Backcrossing

Abstract: In the process (BC3F1 generation) of backcrossing an Avena isolate of Pyricularia oryzae with a Triticum isolate, color mutants with white mycelia were obtained. These white mutants lacked virulence on all (31/31) hexaploid and most (28/32) tetraploid wheat lines tested. In a BC4F1 population, white and black cultures segregated in a 1:1 ratio, suggesting that the mutant phenotype is controlled by a single gene. Furthermore, the mycelial color was perfectly linked with avirulence in the BC4F1 population; white… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 24 publications
0
6
0
1
Order By: Relevance
“…Therefore, MoL population massively built up on the variety and mutations occurred in PWT3, resulting in pwt3-carrying MoL isolates that are virulent even to wheat cultivars with Rmg6, turning MoL into MoT (Inoue et al, 2017). RmgTd(t) was detected by a mutant isolate from a cross between MoA and MoT, which was avirulence to most bread and durum wheat cultivars barring few susceptible tetraploid wheat cultivars (Cumagun et al, 2014).…”
Section: Resistance Mechanism: Major Vs Minor Genesmentioning
confidence: 99%
“…Therefore, MoL population massively built up on the variety and mutations occurred in PWT3, resulting in pwt3-carrying MoL isolates that are virulent even to wheat cultivars with Rmg6, turning MoL into MoT (Inoue et al, 2017). RmgTd(t) was detected by a mutant isolate from a cross between MoA and MoT, which was avirulence to most bread and durum wheat cultivars barring few susceptible tetraploid wheat cultivars (Cumagun et al, 2014).…”
Section: Resistance Mechanism: Major Vs Minor Genesmentioning
confidence: 99%
“…Recently, Juliana et al (2019) reported a prominent role of the 2NS/2AS translocation in CIMMYT germplasm, conferring yield advantage, lodging resistance, along with blast and rust resistance. Apart from the 2NS/2AS translocation, there have been very limited blast resistance genes identified for MoT, i.e., Rmg2 , Rmg3 , Rmg7 , Rmg8 , RmgTd(t) , and RmgGR119 ( Zhan et al, 2008 ; Cumagun et al, 2014 ; Tagle et al, 2015 ; Cruz et al, 2016 ; Wang et al, 2018a ). However, most of these genes have been overcome by new MoT isolates and only Rmg8 and RmgGR119 remained to be validated in field experiments with new MoT isolates.…”
Section: Introductionmentioning
confidence: 99%
“…So far, most genetic studies for WB resistance were performed at the seedling stage, where the host–pathogen interaction appeared to follow the gene-for-gene model (Anh et al 2015 ). The resistance genes identified in such experiments are Rmg2 , Rmg3 , Rmg7 , Rmg8 , RmgTd(t) and RmgGR119 (Zhan et al 2008 ; Cumagun et al 2014 ; Tagle et al 2015 ; Cruz et al 2016b ; Wang et al 2018a ) for host resistance against MoT, and Rmg1 , Rmg4 , Rmg5 , Rmg6 (Hau et al 2007 ; Nga et al 2009 ; Vy et al 2014 ) for resistance against non-MoT strains of M. oryzae . Of these genes, Rmg7 , Rmg8 and RmgGR119 also conferred resistance at the adult plant stage against spike infection by MoT, but Cruz and Valent ( 2017 ) pointed out that the resistance conferred by Rmg7 has been overcome by recent MoT isolates, whereas Rmg8 and RmgGR119 remain to be tested with the new MoT isolates.…”
Section: Introductionmentioning
confidence: 99%